The new Unimore interdisciplinary teaching on transversal sustainability skills - Grazia Ghermandi; Francesca Despini (Journal of Sustainability Perspectives, 2022)
The global situation of the Covid-19 pandemic has changed several aspects of University life and management. In this context, the University of Modena and Reggio Emilia (Unimore) has introduced a new course for all of its students called "Transversal Skills on Sustainability". This course consists of 13 Modules offered by the various Unimore Departments to address the issue of Sustainability at 360 degrees. Each Department offers a thematic module concerning Sustainability in its own field of study and research. The course ranges from engineering issues with renewable energy, waste, air quality, to economics and sustainable finance. In addition, the course deals with issues related to sustainability in the medical, chemical and legal fields and many others. In this first year of delivery, this teaching has proven to be highly appreciated among students. Over 950 students have enrolled in teaching for the 2020/2021 academic year. Enrolled students come from all areas of the university: there are students of engineering, geology, economics, chemistry, but also of medicine, pharmacy, and many others.Keyword: Education, Sustainability, Multidisciplinary, global approach